Identification and Characterization of TEX101 in Bovine Epididymal Spermatozoa - Subir K. Nagdas; Eric L. McLean; Leeá P. Richardson; Samir Raychoudhury (Biochemistry Research International)
Several studies exhibit the presence of Ricinus Communis Agglutinin I (RCA) binding glycocalyx in mammalian spermatozoa. However, the molecular characterization of RCA binding glycocalyx in sperm membranes and its mechanism of action are poorly understood. The objective of the study was to identify and to characterize RCA binding glycoprotein of the bovine sperm plasma membranes (PM). Lectin blots of caput and cauda sperm PM revealed a 38 kDa polypeptide exhibiting the highest affinity to RCA among the several major RCA binding polypeptides. The 38 kDa RCA binding polypeptide of cauda sperm PM was purified and exhibited a charge train of three distinct spots with isoelectric points (pH 5.3 and 5.8). Proteomic identification yielded ten peptides that matched the sequence of Testis Expressed 101 protein (TEX101). Western blots data revealed that bovine sperm TEX101 is present in both testicular and epididymal sperm PM fractions. The native TEX101 polypeptide contains ~17 kDa N-linked oligosaccharides and the polypeptide is anchored to sperm membrane via a glycosylphosphatidylinositol lipid linkage. Immunofluorescence staining of sperm with anti-TEX101 demonstrated that the polypeptide is localized at the head of cauda sperm. Our biochemical results provide evidence on the presence of TEX101 in bovine epididymal sperm plasma membranes and may have a potential role in sperm-egg interaction.